Identification of the high-affinity tolbutamide site on the SUR1 subunit of the K(ATP) channel. - Ashfield, R; Gribble, F; Ashcroft, S; Ashcroft, F (1999)
ATP-sensitive potassium channels (K(ATP)) are formed from four pore-forming Kir6.2 subunits complexed with four regulatory sulfonylurea receptor subunits (SUR1 in pancreatic beta-cells, SUR2A in heart). The sensitivity of the channel to different sulfonylureas depends on the SUR isoform. In particular, Kir6.2-SUR1 but not Kir6.2-SUR2A channels are blocked by tolbutamide with high affinity. We made chimeras between SUR1 and SUR2A to identify the region of the protein involved in high-affinity tolbutamide block. Chimeric SURs were coexpressed with Kir6.2 in Xenopus oocytes, and macroscopic currents were measured in inside-out membrane patches. High-affinity tolbutamide inhibition could be conferred on SUR2A by replacing transmembrane domains (TMs) 14-16 with the corresponding region of SUR1. Conversely, high-affinity tolbutamide inhibition of SUR1 was abolished by replacing TMs 13-16 with the corresponding SUR2A sequence, or by mutating a single serine residue within this region to tyrosine (S1237Y). Binding of [3H]glibenclamide to membranes expressing SUR1 was abolished concomitantly with the loss of high-affinity tolbutamide block. These results suggest that a site in the COOH-terminal set of TMs of the SUR1 subunit of the K(ATP) channel is involved in the binding of tolbutamide and glibenclamide.